Development of Human-Derived Cell Culture Lines for Recurrent Respiratory Papillomatosis. (October 2018) - Attra, James; Hsieh, Li-En; Luo, Linda; Mo, Jun Qin; Brigger, Matthew; Liu, Yu-Tsueng; Pransky, Seth
Recurrent respiratory papillomatosis (RRP) is mainly caused by human papillomavirus (HPV) 6 and 11. While various adjuvant therapies have been reported, no effective therapy has been documented to universally "cure" this disease. In the era of precision medicine, it would be valuable to identify effective intervention based on drug sensitivity testing and/or molecular analysis. It is essential to be able to successfully carry out in vitro culture and expand tumor cells directly from patients to accomplish this goal. Here we report the result of successful culture of HPV-infected cell lines (success rate 70%, 9/13) that express the E6/E7 RNA transcript, using pathologic tissue biopsies from patients treated at our institution. The availability of such a system would enable ex vivo therapeutic testing and disease modeling.